Absence of disparities in anthropometric measures among Chilean indigenous and non-indigenous newborns - Kaufman Jay S; Bustos Patricia; Amigo Hugo (BMC, 2010)
Abstract Background Studies throughout North America and Europe have documented adverse perinatal outcomes for racial/ethnic minorities. Nonetheless, the contrast in newborn characteristics between indigenous and non-indigenous populations in Latin America has been poorly characterized. This is due to many challenges, including a lack of vital registration information on ethnicity. The objective of this study was to analyze trends in anthropometric measures at birth in Chilean indigenous (Mapuche) and non-indigenous children over a 5-year period. Methods We examined weight and length at birth using information available through a national data base of all birth records for the years 2000 through 2004 (n = 1,166.513). Newborns were classified ethnically according to the origins of the parents' last names. Result The average birthweight was stable over the 5 year period with variations of less than 20 g in each group, and with mean values trivially higher in indigenous newborns. The proportion weighing less than 2500 g at birth increased modestly from 5.2% to 5.6% in non-indigenous newborns whereas the indigenous births remained constant at 5.2%. In multiple regression analyses, adjusting flexibly for gestational age and maternal characteristics, the occurrence of an indigenous surname added only 14 g to an average infant's birthweight while holding other factors constant. Results for length at birth were similar, and adjusted time trend variation in both outcomes was trivially small after adjustment. Anthropometric indexes at birth in Chile are quite favorable by international standards. Conclusion There is only a trivial degree of ethnic disparity in these values, in contrast to conditions for ethnic minorities in other countries. Moreover, these values remained roughly constant over the 5 years of observation in this study.